ChemInform Abstract: Complex Open‐Framework Germanate Built by 8‐Coordinated Ge10 Clusters. Issue 7 (22nd February 2013) - Yue, Huijuan; Peskov, Maxim V.; Sun, Junliang; Zou, Xiaodong
Abstract The new compound [(C5H14N2)2 (C5H12N2)0.5 (H2O)2.5] [Ge12.5O26(OH)2] with three‐dimensional 10‐ and 11‐ring channels is hydrothermally synthesized from mixtures of GeO2, 2‐methylpiperazine, and H2O (autoclave, 160 °C, 7 d).